1995
DOI: 10.1302/0301-620x.77b2.7706351
|View full text |Cite
|
Sign up to set email alerts
|

Rotator-cuff changes in asymptomatic adults. The effect of age, hand dominance and gender

Abstract: We studied the integrity of the rotator cuff in both dominant and non-dominant shoulders of 90 asymptomatic adults between the ages of 30 and 99 years using ultrasound. The criteria for diagnosis had been validated on unembalmed cadaver specimens. We found no statistically significant difference in the incidence of impingement findings between dominant and non-dominant arms or between genders. The prevalence of partial-or full-thickness tears increased markedly after 50 years of age: these were present in over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

24
469
2
25

Year Published

1999
1999
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 757 publications
(520 citation statements)
references
References 10 publications
24
469
2
25
Order By: Relevance
“…Aging in tendons is characterized by an increased susceptibility to injury likely resulting from changes in mechanical properties (Milgrom et al 1995;Dressler et al 2002;Jarvinen et al 2005;Wood et al 2011). In order to gain insights into the basis for the age-related changes in tendon mechanical properties, the current study evaluated the changes in the expression levels and localization of proteins known to be critical components of tendon function (collagens, Eln, PRG4) as well as growth factors that regulate expression of ECM proteins in tendons (TGFb1, CTGF, SDF1).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Aging in tendons is characterized by an increased susceptibility to injury likely resulting from changes in mechanical properties (Milgrom et al 1995;Dressler et al 2002;Jarvinen et al 2005;Wood et al 2011). In order to gain insights into the basis for the age-related changes in tendon mechanical properties, the current study evaluated the changes in the expression levels and localization of proteins known to be critical components of tendon function (collagens, Eln, PRG4) as well as growth factors that regulate expression of ECM proteins in tendons (TGFb1, CTGF, SDF1).…”
Section: Discussionmentioning
confidence: 99%
“…Less widely appreciated are marked increases in the occurrence of tendinopathy and rupture with age (Jarvinen et al 2005). Some estimates place the incidence as high as 50 % of people in their 70s and 80 % of those in their 80s suffer from rotator cuff injuries (Milgrom et al 1995). Tendons transmit muscle forces to the skeleton to produce joint torques and generate movement.…”
Section: Introductionmentioning
confidence: 99%
“…The natural history of rotator cuff disease and shoulder magnetic resonance imaging, ultrasound, and arthrography data from asymptomatic individuals suggest that full-thickness rotator cuff tears are extremely uncommon in patients under the age of forty years [18][19][20][21] . Because tearing is so uncommon in this young age group, a genetic predisposition might be more likely to be exhibited in this group, as we observed.…”
Section: Discussionmentioning
confidence: 99%
“…Early onset of a disease has been determined to have an increased predisposition for a genetic contribution in several diseases including breast cancer and heart disease [15][16][17] . The rate of rotator cuff disease increases with age, usually starting around the age of forty [18][19][20][21] . Because age is a risk factor for rotator cuff disease, and early onset disease may indicate a stronger genetic contribution, we also separately analyzed patients who were diagnosed as having rotator cuff disease early (before the age of forty years).…”
Section: Relative Risks In Relativesmentioning
confidence: 99%
“…These studies, often relying on abnormalities in the asymptomatic shoulder, suggest that atraumatic rotator cuff tears are part of the normal aging process in many individuals [1]. In a systematic review investigating the prevalence of rotator cuff disease with increasing age, Teunis et al showed that abnormalities ranged from 9.7% in patients aged 20 years and younger and increased to 62% in patients of 80 years and older [2].…”
Section: Introductionmentioning
confidence: 99%